Influence of pretreatments for extraction of lipids from yeast by using supercritical carbon dioxide and ethanol as cosolvent - Hegel, Pablo Ezequiel (2011)
Saccharomyces cerevisiae is one of the most studied and industrially exploited yeast. It is a non-oleaginous yeast whose lipids are mainly phospholipids. In this work, the extraction of yeast lipids by supercritical carbon dioxide (SCCO2) and ethanol as a co-solvent was studied. In particular our attention was focused on the selectivity toward triglycerides, and in a subsequent extraction of the phospholipids present in the yeast. Indeed CO2 is a non-polar solvent and is not an efficient solvent for the extraction of phospholipids. However, SCCO2 can be used to extract neutral lipids, as triglycerides, and the addition of polar co-solvents like ethanol, at different compositions, allows a more efficient extraction of triglycerides, and also an extraction-fractionation of phospholipids. In this work SCCO2 extractions of a specific membrane complex of S. cerevisiae, obtained from an industrial provider, were carried out at 20 MPa and 40 °C, using ethanol as a co-solvent (9%, w/w). It was shown that different pretreatments are necessary to obtain good extraction yields and have a great impact on the extraction. The kinetic of the extractions were successfully modeled using Sovova's model. From the fitting of the main parameters of the model it was possible to compare the effects of the pretreatments over the yeast material, and to better understand the extraction process. Among the seven tested pretreatments the more appropriate was found to be an acid hydrolysis followed by a methanol maceration.